LOGIC, MYSTERY, AND HUMANITY: AN ANALYSIS OF SIR ARTHUR CONAN DOYLE’S SHERLOCK HOLMES - Visola Hamidova; Shavkatov Sherzod Shavkatovich (TADQIQOTLAR, 2026)
Abstract: Sir Arthur Conan Doyle’s Sherlock Holmes stories represent one of the most enduring and influential contributions to world literature. From the first novel published in 1887 to the final collections, these works have not only shaped the development of the detective genre but have left a profound mark on modern culture as a whole. This article examines the defining characteristics of the Sherlock Holmes figure, the literary techniques employed by Doyle, and the broader socio-cultural significance of the canon. Particular attention is paid to Holmes’s analytical intellect, his relationship with Dr. Watson, and the ways in which the stories reflect Victorian society. The study seeks to explain why the Holmes character has remained relevant for over 135 years, arguing that his lasting appeal lies in the combination of extraordinary rationalism and deeply human contradiction.